ChemInform Abstract: Chemistry and Biochemistry of 13C Hyperpolarized Magnetic Resonance Using Dynamic Nuclear Polarization. Issue 18 (17th April 2014) - Keshari, Kayvan R.; Wilson, David M.
Abstract Review: 229 refs.